2019
DOI: 10.1093/tcbh/hwz016
|View full text |Cite
|
Sign up to set email alerts
|

‘Race’, Black Majority Churches, and the Rise of Ecumenical Multiculturalism in the 1970s

Abstract: At the beginning of the 1970s, relations between the historic British churches and the new black-led churches were usually non-existent or marked by prejudices or ambivalences. This article examines the emergence, development, and significance of a cross-cultural ecumenical dialogue sponsored by the British Council of Churches. It places this in a context of both growing white liberal interest in the ‘multi-racial’ society and the increasing public assertiveness of collective black Christian consciousness. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…This understanding, then, begets a consideration of race as well, given that race and religion are co-constituted, meaning they are "defined, in part, by each other, both in their meanings and in their political effects" (Jacobson and Wadsworth 2012, p. 4). If religious identity is a potential explanation for political socialization and mobilization, then so too must we consider the impact of social capital, which is a measure of one's dedication to and relationship with their community-and those who help provide their identity (Alba et al 2009;Gordon 1964;Haddad et al 2003;Lin 2001). Furthermore, places of worship have been argued to be the largest repository of social capital in the U.S. (Gordon 1964;Brady et al 1995;Putnam 2000), and social capital has consistently been found to promote civic engagement (Wong et al 2011;Djupe and Calfano 2012;Ocampo et al 2018).…”
mentioning
confidence: 99%
“…This understanding, then, begets a consideration of race as well, given that race and religion are co-constituted, meaning they are "defined, in part, by each other, both in their meanings and in their political effects" (Jacobson and Wadsworth 2012, p. 4). If religious identity is a potential explanation for political socialization and mobilization, then so too must we consider the impact of social capital, which is a measure of one's dedication to and relationship with their community-and those who help provide their identity (Alba et al 2009;Gordon 1964;Haddad et al 2003;Lin 2001). Furthermore, places of worship have been argued to be the largest repository of social capital in the U.S. (Gordon 1964;Brady et al 1995;Putnam 2000), and social capital has consistently been found to promote civic engagement (Wong et al 2011;Djupe and Calfano 2012;Ocampo et al 2018).…”
mentioning
confidence: 99%